Paradikma Guru Dalam Bimbingan Konseling Sekolah Dasar di MIM 4 Brangsi Kab. Lamongan - Al Ibad, M. Kamal; Zativalen, Oriza (Primera Educatia Mandalika: Elementary Education Journal, 2024)
Students in the current era need guidance and counseling services to overcome student problems. This research aims to describe the role of teachers in guidance and counseling for the formation of moral values ​​in students in elementary schools. The method in this research is descriptive qualitative. The data source for this research is the homeroom teacher of classes 1, 2 and 3. The research instruments are teacher interviews, teacher observations and student observations. The results of this research are (1) guidance counseling carried out by teachers is able to develop the moral values ​​of students, (2) the role of teachers in implementing guidance counseling is to guide, remind, give advice and provide motivation to students, (3) providing instilling the concept of democracy, developing self-understanding through students' lives, (4) teachers also familiarize students with moral values.